Pelatihan Kewirausahaan Syariah Berbasis Al-Islam dan Kemuhammadiyahan bagi Siswa SMA Muhammadiyah 9 Makassar sebagai Upaya Penumbuhan Jiwa Wirausaha Islami Sejak Dini - Amanda Fikria; Syamsiah, Syamsiah; Hamida Wokas; jasri, jasri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This community service activity carried out at SMA Muhammadiyah 9 Makassar aims to increase students' understanding of the concept of sharia entrepreneurship, foster innovation and creativity, and provide motivation and support in shaping an independent and ethical entrepreneurial spirit. Sharia-based entrepreneurship education emphasizes the importance of conducting business in accordance with Islamic principles, such as honesty, trustworthiness, justice, and social benefit. This activity was implemented through a series of stages including observation, interactive material presentation, direct practice in making creative products, and evaluation. Students learned about the meaning of sharia entrepreneurship, Muhammadiyah business principles, and the role of entrepreneurship in empowering the ummah. The results of the activity showed an increase in students' knowledge, interest, and confidence to start simple, ethical business ventures. It is hoped that this activity will become the foundation for building future Muslim entrepreneurs who contribute to sustainable economic growth.